COVID-19 Vaccination and Asymptomatic Infection: Effect of BNT162b2 mRNA Vaccine on the Incidence of COVID-19 and Duration of Sick Leave Among Healthcare Workers. Issue 12 (17th December 2021) - Prato', Simone; Paladino, Maria Emilia; Riva, Michele Augusto; Belingheri, Michael
Abstract : Objective: To determine the incidence of COVID-19 and the duration of sick leave among asymptomatic healthcare workers (HCWs) after vaccination with BNT162b2. Methods: From October 2020 to March 2021, we determined the incidence of COVID-19 in a cohort of 671 asymptomatic HCWs before and after the vaccination. We also analyzed the days required to obtain a negative RT-PCR result after infection. Results: Prior to vaccination 105 (15.6%) HCWs were positive. Positive cases were reduced to 42 (7.5%) after the vaccination period ( P < 0.0001). A negative RT-PCR was observed at the first control in 80% of vaccinated HCWs and only in 37% before vaccination. Conclusions: Even in case of asymptomatic infection, vaccinated HCWs have a reduced incidence and a shorter period of sick leave than before vaccination, suggesting vaccination impacts on the sustainability of the health system and labor costs.